دراسة تأثير ظروف التّخزين على تحرّر الدّوكسيسكلين من الكبسولات الجيلاتينيّة الصّلبة - عبود, آيات; ابراهيم, وهاد; فاضل, هبة (Latakia University Journal -Medical Sciences Series, 2016)
تعتبر التصالبات التي تحدث في قشرة الكبسولات الجيلاتينية ظاهرة شائعة تؤدي إلى انخفاض معدلات تحرر الدواء. تهدف هذه الدراسة إلى معرفة تأثير درجات الحرارة المرتفعة والرطوبة العالية على تحرر الدوكسيسكلين من الكبسولات الجيلاتينية الصلبة. تم تخزين العبوات الحاوية على الكبسولات في الظروف (40 ⁰C & 75% RH) ، (40 ⁰C & 60% RH)، كما تم التخزين على الرف مع مراقبة دورية لدرجة الحرارة والرطوبة بهدف محاكاة ظروف التخزين في المنزل وبعض الصيدليات. أظهرت النتائج انخفاض الكمية المتحررة من الدوكسيسكلين بمقدار 40% من الكبسولات المخزنة في الظروف (40 ⁰C & 75% RH) بعد 7 أشهر، كما انخفضت الكمية المتحررة بمقدار 33% من الكبسولات التي تم تخزينها في الظروف (40 ⁰C & 60% RH) بعد 7 أشهر. في حالة التخزين على الرف تعرضت العبوات الحاوية على الكبسولات لدرجات حرارة تراوحت بين (21-30 ⁰C) ورطوبة نسبية تراوحت بين (30-78%) لمدة 6 أشهر فلم يحدث إلا تغير بسيط في معدلات التحرر.The cross-linking of Gelatin capsule shell is a common phenomenon that results in decreasing drug release rates. This study aims to reveal the effect of elevated temperatures and high humidity on doxycycline release from hard gelatin capsules. The boxes of capsules were stored in the conditions (40 ⁰C & 75% RH), (40 ⁰C & 60% RH). They were also stored on the shelf with periodical control of temperature and humidity to simulate storage conditions in home and some pharmacies. The results demonstrated about 40% reduction in the released amount of doxycycline from capsules stored under (40 ⁰C & 75% RH) after 7 months. The released amount also decreased about 33% from capsules stored under (40 ⁰C & 60% RH) after 7 months. However, when the boxes of capsules were stored on the shelf, they exposed to temperatures ranged between (21-30 ⁰C) and relative humidity ranged between (30-78%) for 6 months but simple change in the release rates was observed.